Pengaruh Pengelolaan Keuangan terhadap Kinerja Karyawan: Studi Kuantitatif pada Karyawan PT. Serim Indonesia - Branch Office Medan - Lina Lina; Daud Arifin; Festin Niat Hasrat Wati Amazihono; Lenny Lenny (JURNAL MANAJEMEN & ORGANISASI REVIEW (MANOR), 2026)
This study aims to determine the effect of financial management on employee performance at PT. Serim Indonesia. The research method used was a quantitative method with an associative approach. Data collection techniques were carried out through the distribution of questionnaires to employees who were selected as research respondents. The research data were analyzed using the Statistical Package for the Social Sciences (SPSS) through validity testing, reliability testing, classical assumption testing, simple linear regression analysis, t-test, and coefficient of determination. The results of the study indicate that financial management has a positive and significant effect on employee performance. This is proven by the results of the t-test which show a significance value smaller than 0.05, meaning that the research hypothesis is accepted. In addition, the results of the simple linear regression analysis show that the better the financial management possessed by employees, the higher the employee performance at PT. Serim Indonesia Branch Office Medan. The coefficient of determination results indicate that financial management is able to explain variations in employee performance, while the remaining percentage is influenced by other factors outside the study. Based on the results of the study, it can be concluded that financial management has an important role in improving employee productivity and work quality. Therefore, companies are expected to pay attention to employees’ financial well-being through financial literacy programs and financial management training to support the improvement of employee performance within the company.